(untitled) (AYUSHDHARA, 2018)
Gridhrasi (Sciatica) is one among the Natamaja vata vyadhis. It is most commonly seen in the society as an eminent problem. The patient is unable to perform his daily routine activity easily. Symptoms seen are Toda (pain), initially affects Sphik (gluteal region) as well as the posterior aspects of the Uru (thigh), Janu (knee), Jangha (calf) and Pada (foot). Though Gridhrasi (Sciatica) is the Vata Vyadhi but Kapha is the Anugata Dosha. So it is classified into 2 types, Vataja and Vata-Kaphaja. Gridhrasi (Sciatica) is one among the severe debilitating disease. Acharaya Sushruta mentioned most of the Hetus (etiology) for Gridhrasi (Sciatica) from which Vata Vaigunya is important to cause disease. Vata is the main culprit in this disease and other Dosha may be involved. Gridhrasi is more common among 30 to 50 years of age group. Gridhrasi (Sciatica) can be correlated with Sciatica in contemporary science. Sciatica is the name given to pain caused by irritation of the sciatic nerve. The sciatic nerve is the longest and widest nerve in the human body. It runs from the lower back, through the buttocks, and down the legs, ending just below the knee. In the present article it’s been highlighted regarding the disease Gridhrasi and its Aharaja Nidanas (dietetic causative factors) as per the scattered references available in the various classical texts.